OPTIMIZATION OF NATURAL URANIUM-FUELED GAS-COOLED FAST REACTOR (GFR) DESIGN WITH MODIFIED CANDLE BURNUP SCHEME WITH VARIABLE ACTIVE REACTOR HEIGHT SIZE - Izzaty Harahap, Dini
One type of generation IV rector is the Gas-Cooled Fast Reactor (GFR) with fast neutron spectrum characteristics. In this final project research, neutronic analysis will be carried out on GFR by varying the ratio of the active core's height to the active core's diameter, the thermal power level, and the reflector's thickness. The observed neutronic parameters include multiplication factor, integral conversion ratio coefficient, burnup level, and atomic density. This study aims to find the optimal design of GFR. The calculation method used involves using the Standard Reactor Analysis Code System (SRAC) program. The burnup scheme in this study uses the M-CANDLE burnup scheme. From the results that have been obtained, it can be known that the Gas Cooled Fast Reactor designed in this study can be operated for up to 100 years with a ratio between the height of the active core per diameter (H/D) which is 4/5 with a height of 128 cm and a diameter of 160 cm. Then on the variation in thermal power, it shows that the thermal power of 500-700 MWt has a multiplication factor value above one, which means that the reactor is already in a supercritical state. Furthermore, in the variation of reflector size, overall, the data obtained for the reflector size range of 80-120 cm did not provide significant differences in each parameter reviewed. From this study, it can be concluded that the designed GFR can operate optimally at the H/D ratio, which is 4/5 with a height of 128 cm and a diameter of 160 cm, in the power range of 500- 700 MWt and a reflector thickness between 90-120 cm.